2022
DOI: 10.31925/farmacia.2022.4.4
|View full text |Cite
|
Sign up to set email alerts
|

Quality by Design Approach for the Development of Salinomycin and Gemcitabine Combination Therapy Liposomes for Colorectal Cancer

Abstract: An ideal cancer treatment would eradicate all types of malignant cells, both rapidly replicating and quiescent stem-like cancer cells. Therefore, a combination of drugs capable of targeting all subtypes of cancer cells could offer a better outcome in cancer. Nano-delivery systems for combination therapy represent more secure and efficient platforms for the delivery of anticancer drugs to tumours. Nanocarrier drug development is a complex process which requires careful design and evaluation at various levels to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
1
1
0
Order By: Relevance
“…Even though authors reported that an increased amount of CHOL leads to an increase in liposome particle size, [28] in our study, this excipient had a negative influence on the size of the liposomes. In accordance with these results, our group observed the same negative influence of CHOL on the size of salinomycin and gemcitabine‐loaded liposomes [29] …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Even though authors reported that an increased amount of CHOL leads to an increase in liposome particle size, [28] in our study, this excipient had a negative influence on the size of the liposomes. In accordance with these results, our group observed the same negative influence of CHOL on the size of salinomycin and gemcitabine‐loaded liposomes [29] …”
Section: Resultssupporting
confidence: 86%
“…group observed the same negative influence of CHOL on the size of salinomycin and gemcitabine-loaded liposomes. [29] The PDI values before extrusion were influenced by the interactive factor X2*X3, which had a negative effect on the response. As the DOTAP and CHOL concentrations increased, the PDI decreased (Figure 1C).…”
Section: Doe: Evaluation Of the Mathematical Models And The Responsesmentioning
confidence: 99%